Pengaruh Corporate Governance terhadap Peringkat Obligasi dan Yield Obligasi - Yudi Santara Setyapurnama; A.M. Vianey Norpratiwi (Jurnal Akuntansi dan Bisnis, 2007)
This paper investigated the effect of corporate governance to bond ratings and bond yield. The proxies of corporate governance are institution ownership, independent committe, audit committee, and managerial ownership. Those proxies are independent variables, and the dependent variables are bond rating and bond yield. Logistic regression (logit) is used to examine first hipothesis, and multiple regression is used to examine second hypothesis. Sample are all bonds that issued period 2001-2003, and data are collected from Surabaya Stock Exchage and PT PEFINDO. The paper proved that implementation of corporate governance influences bond ratings and yields. The existence of independent committee have positive effect to bond rating but the opposite effect is to bond yield. The better of corporate governance implementation the higher bond ratings, but bond yields will decresase.. The existence of audit committee have negative effect to bond yield. It concluded that the existence of aucit committee give effect for investor judgement.